2022
DOI: 10.1093/jipm/pmac026
|View full text |Cite
|
Sign up to set email alerts
|

History Does Not Repeat Itself; It Rhymes: Range Expansion and Outbreak of Plecia longiforceps (Diptera: Bibionidae) in East Asia

Abstract: Plecia longiforceps Duda (Diptera: Bibionidae) is reported for the first time from Korea. P. longiforceps has been previously known from the East Asian subtropics, south of the 33rd parallel, including southeastern China, Taiwan, and the Ryukyu Islands of Japan. An integrative taxonomic approach based on morphological examination of male genitalia and molecular analysis of mitochondrial cytochrome c oxidase subunit I gene sequences confirms the species identification. The recent outbreak of P. longiforceps in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…According to a previous study conducted in 2022, lovebugs collected from various regions of Korea were identified as either P. longiforceps or P. thulinigra . Specifically, those collected from the Seoul metropolitan area were identified as P. longiforceps , which is consistent with the findings of the present study ( 4 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…According to a previous study conducted in 2022, lovebugs collected from various regions of Korea were identified as either P. longiforceps or P. thulinigra . Specifically, those collected from the Seoul metropolitan area were identified as P. longiforceps , which is consistent with the findings of the present study ( 4 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the summer of 2022, several lovebugs were observed in northwestern Seoul, and in the summer of 2023, this phenomenon also occurred and spread to southern Seoul. Because lovebug outbreaks have been a very rare phenomenon in Korea, their presence has caused fear among residents even if they do not cause immediate health problems in humans ( 4 ). Lovebugs, first detected in Florida in 1949, have been observed two times annually at an exceedingly high abundance since the mid-1960s ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there was a recent outbreak of love bugs, Plecia longiforceps, in the ROK [99], and the nonnative species A. hors eldii was identi ed on Jeju Island in 2019 [36]; these species are distributed mainly in southern China, Taiwan, and the Okinawa archipelago. These cases suggest the potential for provisional or temporary spread of nonnative species to the ROK.…”
Section: Discussionmentioning
confidence: 99%